2018
DOI: 10.1002/cbf.3365
|View full text |Cite
|
Sign up to set email alerts
|

NAIF1 suppresses osteosarcoma progression and is regulated by miR‐128

Abstract: Nuclear apoptosis‐inducing factor 1 (NAIF1) acts as an oncogene and involves in tumorigenesis in several cancers. However, the expression and mechanism of NAIF1 in osteosarcoma remains unclear. In this study, we demonstrated the downregulation of NAIF1 expression in both osteosarcoma tissues and cell lines. We next explored the potential role of NAIF1 in osteosarcoma cell proliferation and migration. The result showed that overexpression of NAIF1 evidently suppressed the cell proliferation and invasion of oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…miRNAs are involved in the diagnosis of OA as well as in its treatment [ 29 , 30 ]. The data in a previous study indicated that the miR-128 downregulation inhibits osteosarcoma cell proliferation and migration phenotype [ 31 ]. Activation of Wnt/β-catenin signaling pathways play essential roles and may rescue chemotherapy drug resistance by targeting Beclin 1 in osteosarcoma cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are involved in the diagnosis of OA as well as in its treatment [ 29 , 30 ]. The data in a previous study indicated that the miR-128 downregulation inhibits osteosarcoma cell proliferation and migration phenotype [ 31 ]. Activation of Wnt/β-catenin signaling pathways play essential roles and may rescue chemotherapy drug resistance by targeting Beclin 1 in osteosarcoma cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the proteomic expression of NAIF1 gene [10][11][12][13][14] . Our results are consistent with the previous studies were done on NAIF1 gene expression showed that, NAIF1 is expressed in both cancer tissue or cancer cell lines and in non-cancerous or normal tissue [10,12] , this expression was strong or high in non-cancerous or normal tissue compared with weak or little seen in cancerous one.…”
Section: Discussionmentioning
confidence: 99%
“…The human gene encoding nuclear apoptosis inducing factor 1 (NAIF1) is located on chromosome 9q34.11, and reported to repress the progression of several human cancers [9,[10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations